Sosialisasi perizinan makanan dan minuman di Dusun Pasrepan, Desa Purwoasri, Kabupaten Malang - Arisandy, Rajulan (Maliki Interdisciplinary Journal, 2023)
Student Work Lecture (KKM) is one manifestation of community service. The presence of the KKM is expected to provide new motivation and innovation in the local village environment. Especially in the development of MSMEs or IKM owned by the community. For example, in Pasrepan Hamlet, Purwoasri Village, and Malang Regency, there are IKMs in the form of Miler Chips, Lidi Noodles, and others. The problem with this IKM is that business owners do not have halal certification for their products and business identification numbers (NIB The purpose of this study is to provide knowledge and understanding regarding the management of product licensing so that the products produced by MSMEs get a distribution rights permit for PIRT (Home Industry Food), Business Identification Number (NIB), and legal Halal Certification. The methods used in this study were field supervision, coordination with interested parties, socialization programs, and implementation of socialization. The method used in this study is a field survey in Pasrepan Hamlet, Purwoasri Village. This was carried out by visiting MSME business owners. This survey has the aim of observing the situation and condition of the community which is planned as the target object, with interested parties. The stated results are that MSME business actors can take care of Company Identification Numbers, Halal certification, and SPP-IRT.